CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF ZnO NANOPARTICLES SYNTHESIZED BY CO PRECIPITATION METHOD - D., Manyasree; P., Kiranmayi; Kolli, Venkata R (International Journal of Applied Pharmaceutics, 2018)
Objective: In the present study the antibacterial activity of zinc oxide (ZnO) nanoparticles was investigated against gram negative (Escherichia coli and Proteus vulgaris) and gram positive (Staphylococcus aureus and Streptococcus mutans) organisms. Methods: The synthesis of ZnO nanoparticles was carried out by co-precipitation method using zinc sulfate and sodium hydroxide as precursors. These nanoparticles were characterized by XRD (X-Ray Diffraction), FTIR (Fourier Transform Infrared Radiation), UV-Visible spectroscopy and SEM (Scanning Electron Microscope) with EDX (Energy Dispersive X-ray analysis). As well as antibacterial activity and minimum inhibitory concentration of the nanoparticles were carried out by agar well diffusion method and broth dilution method respectively against gram negative (Escherichia coli and Proteus vulgaris) and gram positive (Staphylococcus aureus and Streptococcus mutans) bacteria. Results: The average crystallite size of ZnO nanoparticles was found to be 35 nm by X-ray diffraction. The vibration bands at 450 and 603 cm-1 which were assigned for ZnO stretching vibration were observed in FTIR spectrum. The optical absorption band at 383 nm was obtained from UV-Visible spectrum. Spherical shape morphology was observed in SEM studies. The antibacterial assay clearly expressed that E. coli showed a maximum zone of inhibition (32Â±0.20 mm) followed by Proteus vulgaris (30Â±0.45 nm) at 50 mg/ml concentration of ZnO nanoparticles. Conclusion: Zinc oxide nanoparticles have exhibited good antibacterial activity with gram negative bacteria when compared to gram positive bacteria.